Analyzing the status of submerged aquatic vegetation using novel optical parameters - Rotta, Luiz H. S. [UNESP]; Mishra, Deepak R.; Alcantara, Enner H. [UNESP]; Imai, Nilton N. [UNESP] (Taylor & Francis Ltd, 2016)
The reservoirs constructed throughout Brazil for electrical power generation following its industrial and socioeconomic development now favour abundant aquatic macrophyte growth. Nova Avanhandava Reservoir is fully inhabited by submerged aquatic vegetation (SAV) that poses serious ecological and economic threats. The overall goal of this study was to assess the radiation availability in the water column in the Nova Avanhandava Reservoir and analyse its influence on SAV development and growth. In addition to the diffuse attenuation coefficient (K-d) and euphotic zone depth (Z(EZ)), optical parameters such as percentage light through the water (PLW) were computed and analysed to achieve the objective. Nineteen sampling locations were considered for both spectroradiometer measurements and water sampling for analytical determination of total suspended solids (TSS) and chlorophyll-a concentration. Depth, SAV height, and precise position were also collected through hydro-acoustic measurements. The upstream region showed the highest TSS and K-d levels compared to the downstream. SAV heights were found to be lower upstream compared to downstream. The growth of tall SAV was favoured by low PLW, which grew taller to intercept required radiation. Locations with high transparency (lower K-d) also favoured the development of tall SAV compared to areas of high K-d. This may mean that low PLW values favour tall SAV growth if K-d is low enough not to hinder this. An inverse relationship between SAV height and attenuation of photosynthetic active radiation (K-d,K-PAR) was observed with a coefficient of determination of R-2=0.56 (p<0.001), demonstrating that SAV height can be estimated using K-d,K-PAR with significant accuracy.